New Nonlinear Systems Admitting Virasoro-Type Symmetry Algebra and Group-Invariant Solutions - Lizhen Wang; Qing Huang; Yanmei Di (Abstract and Applied Analysis)
With the aid of symbolic computation by Maple, we extend the application of Virasoro-type symmetry prolongation method to coupled systems with two-component nonlinear equations. New nonlinear systems admitting infinitely dimensional centerless Virasoro-type symmetry algebra are constructed. Taking one of them as an example, we present some group-invariant solutions to one of the new model systems.